A highly stable and efficient quasi solid state dye sensitized solar cell based on Polymethyl methacrylate(PMMA)/Polyaniline Nanotube(PANI-NT) gel electrolyte. (20th December 2016) - Mohan, Kiranjyoti; Bora, Anindita; Nath, Bikash Chandra; Gogoi, Pronob; Saikia, Bhaskar Jyoti; Dolui, Swapan Kumar
Graphical abstract: Abstract: A novel polymer gel electrolyte (PGE) based on polymethyl methacrylate (PMMA)/polyaniline nanotube (PANI-NT) with LiI/I2 as a redox couple and 4-tertbutylpyridine as additive was prepared in a solvent mixture of N-methyl 2-pyrrolidone (NMP) and acetonitrile. PMMA and PANI-NT were characterized using Fourier transform infrared spectroscopy. Different amounts of PANI-NT (0.15, 0.20, 0.25 and 0.30 wt%) were used to optimize the ionic conductivity of the polymer gel electrolyte. Electrochemical Impedance Spectroscopy (EIS) showed that the introduction of PANI-NT in the PMMA based gel electrolyte enhanced the ionic conductivity of the gel electrolyte. The surface morphology of gel electrolytes was studied using scanning electron microscopy. A series of Dye sensitized solar cells (DSSCs) were fabricated employing the foresaid gel electrolytes with different weight percentages of PANI-NT. The cell performance of the optimized DSSC was investigated by current density vs. voltage (J-V) characteristics. The optimized system exhibited an open circuit voltage of 0.75 V, short circuit current density of 9.80 mA cm −2, fill factor of 0.68 and the photo-conversion efficiency of 5.11% under irradiation of 100 mW cm −2 and air mass (AM) 1.5. EIS was used to study the charge transfer processes in the DSSCs under irradiation. The increment of PANI-NT in the PMMA based gel electrolytes reduces the charge transfer (Rct ) process, resulting enhancement of the device efficiency. The long term stability study of the DSSCs shows that the PMMA/PANI-NT based gel electrolyte have commendable durability as compared to the liquid electrolyte.